Large‐scale phosphomimetic screening identifies phospho‐modulated motif‐based protein interactions - Johanna Kliche; Dimitriya Hristoforova Garvanska; Leandro Simonetti; Dilip Badgujar; Doreen Dobritzsch; Jakob Nilsson; Norman E Davey; Ylva Ivarsson (Molecular Systems Biology)
Abstract Phosphorylation is a ubiquitous post‐translation modification that regulates protein function by promoting, inhibiting or modulating protein–protein interactions. Hundreds of thousands of phosphosites have been identified but the vast majority have not been functionally characterised and it remains a challenge to decipher phosphorylation events modulating interactions. We generated a phosphomimetic proteomic peptide‐phage display library to screen for phosphosites that modulate short linear motif‐based interactions. The peptidome covers ~13,500 phospho‐serine/threonine sites found in the intrinsically disordered regions of the human proteome. Each phosphosite is represented as wild‐type and phosphomimetic variant. We screened 71 protein domains to identify 248 phosphosites that modulate motif‐mediated interactions. Affinity measurements confirmed the phospho‐modulation of 14 out of 18 tested interactions. We performed a detailed follow‐up on a phospho‐dependent interaction between clathrin and the mitotic spindle protein hepatoma‐upregulated protein (HURP), demonstrating the essentiality of the phospho‐dependency to the mitotic function of HURP. Structural characterisation of the clathrin‐HURP complex elucidated the molecular basis for the phospho‐dependency. Our work showcases the power of phosphomimetic ProP‐PD to discover novel phospho‐modulated interactions required for cellular function.